Mechanical properties of ceramic powder based geopolymer mortars - Kaya Mehmet (Magazine of Civil Engineering, 2022)
In this study, the properties of geopolymer mortars produced by activating ceramic powder with Sodium Hydroxide (NaOH) and Sodium Silicate (Na2SiO3) were investigated. Activator mixture was prepared by mixing NaOH containing 11 %, 13 % and 15 % sodium in proportion to the binder weight and Na2SiO3 in different proportions. The silicate modulus of the activator mixtures were set at ratios ranging from 0 to 0.3. Geopolymer samples were prepared by mixing ceramic powder with activator, water and sand in a standard cement mixer. After fresh mortar mixtures were placed in the molds, they were cured at 105 °C for 24 hours. The samples were taken out of the molds after curing. They were kept at room temperature for up to 28 days. Then, the samples underwent unit weight test, apparent porosity, water absorption ratio, ultrasound pulse velocity, flexural and compressive strength tests. As a result of the tests, compressive strength between 10.42 MPa and 41.53 MPa, flexural strength between 2.34 MPa and 10.38 MPa were determined. Optimum mixing ratio and strength values were determined.